DNA mutation motifs in the genes associated with inherited diseases - Růžička, Michal; Kulhánek, Petr; Radová, Lenka; Čechová, Andrea; Špačková, Naďa; Fajkusová, Lenka; Réblová, Kamila (PloS one, 2017)
Mutations in human genes can be responsible for inherited genetic disorders and cancer. Mutations can arise due to environmental factors or spontaneously. It has been shown that certain DNA sequences are more prone to mutate. These sites are termed hotspots and exhibit a higher mutation frequency than expected by chance. In contrast, DNA sequences with lower mutation frequencies than expected by chance are termed coldspots. Mutation hotspots are usually derived from a mutation spectrum, which reflects particular population where an effect of a common ancestor plays a role. To detect coldspots/hotspots unaffected by population bias, we analysed the presence of germline mutations obtained from HGMD database in the 5-nucleotide segments repeatedly occurring in genes associated with common inherited disorders, in particular, the PAH, LDLR, CFTR, F8, and F9 genes. Statistically significant sequences (mutational motifs) rarely associated with mutations (coldspots) and frequently associated with mutations (hotspots) exhibited characteristic sequence patterns, e.g. coldspots contained purine tract while hotspots showed alternating purine-pyrimidine bases, often with the presence of CpG dinucleotide. Using molecular dynamics simulations and free energy calculations, we analysed the global bending properties of two selected coldspots and two hotspots with a G/T mismatch. We observed that the coldspots were inherently more flexible than the hotspots. We assume that this property might be critical for effective mismatch repair as DNA with a mutation recognized by MutSα protein is noticeably bent.
Keywords: Models, Molecular; Humans; LDL-receptory; zárodečné mutace; lidé; molekulární modely; Factor VIII; DNA; simulace molekulární dynamiky; Nucleotide Motifs; Cystic Fibrosis Transmembrane Conductance Regulator; Germ-Line Mutation; Receptors, LDL; Molecular Dynamics Simulation; Genetic Predisposition to Disease; genetická predispozice k nemoci; protein CFTR; konformace nukleové kyseliny; faktor VIII; Nucleic Acid Conformation; nukleotidové motivy